Исследование НДС биметаллического вагонного колеса при технологических и эксплуатационных нагрузках - Щепкин, Александр Витальевич; Андреев, Арнольд Георгиевич (НТУ "ХПИ", 2003)
This work is devoted to the research of the stress-strain state of an experimental bimetallic carload of the railway car during thermal assembly, optimization of a temperature field in a wheel during its heating for its fitting on to an axis, while in service during interaction with a rail and during heating of bandage during braking
Keywords: колесная пара; железнодорожный подвижной состав; жесткость колеса; напряженно-деформированное состояние; тележка вагона